Genetic diversity in Colletotrichum gloeosporioides from Stylosanthes spp. at centers of origin and utilization - Weeds, P.L.; Chakraborty, S.; Fernandes, C.D.; Charchar, Maria José; Ramesh, C.R.; Kexian, Y.; Kelemu, Segenet (Scientific Societies, 2003)
Using molecular markers, this work compares the genetic diversity in Colletotrichum gloeosporioides infecting species of the tropical forage legume Stylosanthes at the center of origin in Brazil and Colombia with that of Australia, China, and India, where Stylosanthes spp. have been introduced for commercial use. There was extensive diversity in the pathogen population from Brazil, Colombia, China, and India. The Australian pathogen population was least diverse probably due to its geographical isolation and effective quarantine. The extensive diversity in China and India means that threats from exotic pathogen races to Stylosanthes pastures can potentially come from countries outside the South American center of origin. In Brazil and India, both with native Stylosanthes populations, a high level of genetic differentiation in the pathogen population was associated with sites where native or naturalized host population was widely distributed. There was limited genetic diversity at germplasm evaluation sites, with a large proportion of isolates having identical haplotypes. This contrasts recent pathogenicity results for 78 of the Brazilian isolates that show hot spots of complex races are more common around research stations where host germplasm are tested, but few are found at sites containing wild host populations. For a pathogen in which the same races arise convergently from different genetic backgrounds, this study highlights the importance of using both virulence and selectively neutral markers to understand pathogen population structure.